Exploring the Cosmology of the Qur'an (Integration of Interpretation and Natural Sciences) - Iik Rifki Alfian Muiz; Ahmad Thoriq Aziz; Abdul hakim; Usman Habibullah; Ahmad Dafari; Mupliha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In general, the Qur'an is defined as a book containing a collection of Allah's words, a miracle revealed to the Prophet Muhammad. The creation of the universe has been explained in the Qur'an with various natural phenomena that are shown to be strong factors to show that this universe has a creator and cannot stand alone. Then, cosmology is a branch of metaphysics, namely as a science that investigates and studies the cosmos (universe) which is usually defined as everything other than God Almighty. This study uses a library research design that aims to obtain information and integrate science and Islam. From these opinions, we can take the understanding that cosmology is the initial theory of the creation of the universe, who created it, when it was created, how the process was and so on. There are several famous theories in the creation of the universe, such as the big bang theory, the steady state theory, the oscillation theory and the balloon theory. Islam and science are two aspects that are always related, the emergence of the discipline of cosmology in natural science as a result of philosophical questions about the creation of the universe. Islam, with its book of guidance, is able to answer and provide a solution to the curiosity of people who question the creation of the universe.